The Effectiveness of Sitaya Miniature Media on the Cognitive Abilities of Group B Children Aged 5–6 Years at Darussalam Islamic Kindergarten, Palangka Raya - Febrianty, Berliana Nansya; Fitriani, Ignatia Imelda (JURNAL PENDIDIKAN, 2025)
Learning media plays an important role in the teaching and learning process. The use of media is expected to create positive impacts, such as a more conducive learning environment, feedback, and optimal outcomes. The Sitaya Miniature Media represents a "Solar System" model. This media is a scaled-down replica of the actual arrangement of planets, designed for classroom use to address limitations of time, space, and sensory experiences. This study aims to examine the effectiveness of the Sitaya miniature media on the cognitive abilities of children in group B aged 5-6 years at TK Islam Darussalam Palangka Raya. This research employs a quantitative approach using an experimental method with a "One Group Pre-Test and Post-Test Design." The sample consists of 17 children from group B at TK Islam Darussalam Palangkaraya, aged 5-6 years. Based on the research findings, it can be concluded from the t-test calculation that the t value obtained is 4.587, while the t table value at a significance level of 5% with 16 degrees of freedom is 2.119. Since t calculated (4.587) > t table (2.119), it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that there is an effectiveness of the Sitaya miniature media on the cognitive abilities of children in group B aged 5-6 years at TK Islam Darussalam Palangkaraya.